Viewing the Unseen: Scrub Encephalopathy as an Important Differential Diagnosis of AES - Mishra, Sidharth Sekhar; Mishra, Reshmi; Nitika, -; Jain, Mukesh; Sahoo, Bandya (Journal of Nepal Paediatric Society, 2017)
Japanese encephalitis (JE) is the important cause of Acute Encephalitis Syndrome (AES). However, in large proportion of AES cases, the specific cause cannot not be established. For this, scrub typhus is one such emerging cause. In line with this, first such case report on AES in Odisha due to scrub encephalopathy in paediatric age group is presented. J Nepal Paediatr Soc 2016;36(3):307-309